Phosphorus status and index for predicting environmental risk of phosphorus leaching in typical vegetable soils of Hangzhou - JIANG Bo; LIN Xian-yong; ZHANG Yong-song (浙江大学学报. 农业与生命科学版)
Chemical analysis was used to study soil phosphorus status and the relationships between agronomic and environmental soil P tests in order to develop an index to assess the environmental risk of P loss potential in typical vegetable soils collected from suburb of Hangzhou. The results show that total soil P (TP) and soil-test P measured with CaCl2-P, Olsen-P and PM3 with a wide range were 0.7-2.9 g·kg-1, 0.48-19.64 mg·kg-1, 10.65-151.60 mg·kg-1 and 50.53-904.95 mg·kg-1, respectively. Of all the tested soils, 72% soils with Olsen-P exceeded agronomically optimum critical level of 60 mg·kg-1. DPSox ranged from 6.91% to 49.15% and DPSM3 ranged from 5.82% to 52.56%. Positive significant relationships were observed between DPS and TP, Olsen-P and PM3. Two methods of DPS calculations were linearly related to another. A split-line mode related soil soluble P concentrations to the Olsen-P concentrations and DPS, indicating that the respective change points were: Olsen-P=76.19 mg·kg-1, DPSox=26%, and DPSM3=22%. Soluble P loss in leaching may be greater in soils with Olsen-P and DPS values that exceed these thresholds than in soils with lower Olsen-P and DPS values. More than 60% of the tested soils exceeded the above Olsen-P and DPS thresholds. It indicated that the environmental Olsen-P threshold is above agronomic optimum soil Olsen-P test value, and therefore, if agricultural soils are below these environmental Olsen-P and DPS thresholds, then adequate crop P supply and environmental protection can both be achieved.